Internalisasi Nilai Sila Ke-2 Pancasila dalam Memperkuat Toleransi di SMP Negeri 5 Balfai Penfui Timur Kupang - Maria Cristina Ngadha; Yulsi Nitte; Vinsen Manek Ati; Sifra Betel Kusmawan; Vinny Christin Nenoharan; Melania Novilia Olinti; Titania Agata Mbeo (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Internalization is the process by which individuals adopt, comprehend, and integrate specific values, norms, or concepts into their personality structure, making them an integral part of their consciousness and daily behavior. This process plays a crucial role in shaping individual identity and fostering social cohesion within society. Internalization typically occurs through various mechanisms, such as formal education, family socialization, social interactions, and personal experiences. This study aims to explore the dynamics of internalization in the contexts of education, culture, and organizations, focusing on factors influencing the success of the internalization process. The findings reveal that effective communication, a supportive environment, and active individual engagement are key elements in achieving successful internalization. These results hold.